2016
DOI: 10.1007/s10562-016-1843-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Average Crystallites Size of Active Phase in Ceria-Supported Cobalt-Based Catalysts by Hydrogen Chemisorption vs TEM and XRD Methods

Abstract: Cobalt catalysts with CeO 2 support, unpromoted and promoted with potassium were prepared by an impregnation method. Reduced catalysts were subjected to hydrogen chemisorption at different temperatures in the range of 313-453 K. Studies have shown that calculated Co crystallites size depends on the temperature of chemisorption. The average of size crystallites of the Co active phase obtained from the total and strong chemisorption data were compared with those from measurements by other techniques, TEM and XRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Although the average cobalt particle size, estimated by H 2 chemisorption, is bigger than that obtained from TEM, the general trend has been preserved. This phenomenon has already been observed in the literature [30], where it was shown that the divergence of Co average size, determined by hydrogen chemisorption and TEM, is definitely higher in the case of small cobalt NPs (e.g., 4-5 nm) than that in the case of larger nanoparticles (≥12 nm). In our case, however, this relation is reversed, i.e., the size of the small particles was estimated quite accurately, while for the larger particles, the discrepancy between the TEM and chemisorption-based size increases.…”
Section: Temperature-programmed Desorption Of Hydrogen (H 2 -Tpd)supporting
confidence: 77%
“…Although the average cobalt particle size, estimated by H 2 chemisorption, is bigger than that obtained from TEM, the general trend has been preserved. This phenomenon has already been observed in the literature [30], where it was shown that the divergence of Co average size, determined by hydrogen chemisorption and TEM, is definitely higher in the case of small cobalt NPs (e.g., 4-5 nm) than that in the case of larger nanoparticles (≥12 nm). In our case, however, this relation is reversed, i.e., the size of the small particles was estimated quite accurately, while for the larger particles, the discrepancy between the TEM and chemisorption-based size increases.…”
Section: Temperature-programmed Desorption Of Hydrogen (H 2 -Tpd)supporting
confidence: 77%
“…However, the general trend has been preserved. Based on the literature data [23], we could explain that the average size of nickel-based nanoparticles estimated from XRD data is congruous with that measured by the TEM method only in the case when there are no very small ones among the crystallites.…”
Section: Tem Investigationmentioning
confidence: 81%
“…The active metal surface area, dispersion and mean Co particle size of catalysts pre‐reduced in situ in H 2 at 420 °C (1 h) were calculated from H 2 chemisorption data obtained by using an ASAP 2020 (Micromeritics) analyser at 130 °C . A H/Co stoichiometry of 1:1 and a spherical shape of the Co particles were used to calculate the mean size.…”
Section: Methodsmentioning
confidence: 99%
“…A H/Co stoichiometry of 1:1 and a spherical shape of the Co particles were used to calculate the mean size. A detailed description of the calculation method has been given elsewhere …”
Section: Methodsmentioning
confidence: 99%